An Exploration of the Dynamic Protection Path of Meibei Village Academy in Ji’an City - Rong, He (Journal of Social Science and Humanities, 2025)
Meibei Ancient Village, located in Qingyuan District, Ji’an City, Jiangxi Province, is a highly representative ancient village of the Jiangyou ethnic lineage and is renowned as “the First Village of Luling Culture”. With a long history dating back to the early Southern Song Dynasty nearly a thousand years ago, Meibei Village boasts a rich cultural heritage, particularly distinguished by its academy culture. The village still preserves several historic academies, including Jingde Academy, Mingxin Academy, Zhenhan Academy, and Yangyuan Academy. These academies witnessed the cultural development of Meibei Village, yet today they have fallen into disrepair and ceased operation. The thesis is based on field research and interviews with local villagers, tracing the historical development of Meibei’s academies and exploring pathways for their modern revitalization.